2019
DOI: 10.1101/746180
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Structural basis for EPC1-mediated recruitment of MBTD1 into the NuA4/TIP60 acetyltransferase complex

Abstract: MBTD1, a H4K20me reader, has recently been identified as a component of the NuA4/TIP60 acetyltransferase complex, regulating gene expression and DNA repair.NuA4/TIP60 inhibits 53BP1 binding to chromatin through recognition of the H4K20me mark by MBTD1 and acetylation of H2AK15, blocking the ubiquitination mark required for 53BP1 localization at DNA breaks. The NuA4/TIP60 non-catalytic subunit EPC1 enlists MBTD1 into the complex, but the detailed molecular mechanism remains incompletely explored. Here, we prese… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…The PHF1 fraction contained the core subunits EZH2, EED and SUZ12 of the PRC2 complex, as well as RBBP4 and the PRC2.1 specific PALI-1/LCOR. The EPC1(1-581) fraction contained all the subunits of NuA4/TIP60 complex except MBDT1, which was expected since it associates through an interaction with EPC1 C-terminus (aa644-672) (Jacquet et al, 2016; Zhang et al, 2020). Strikingly, the EPC1-PHF1 fraction contained subunits of both the TIP60 and PRC2.1 complexes.…”
Section: Resultsmentioning
confidence: 88%
“…The PHF1 fraction contained the core subunits EZH2, EED and SUZ12 of the PRC2 complex, as well as RBBP4 and the PRC2.1 specific PALI-1/LCOR. The EPC1(1-581) fraction contained all the subunits of NuA4/TIP60 complex except MBDT1, which was expected since it associates through an interaction with EPC1 C-terminus (aa644-672) (Jacquet et al, 2016; Zhang et al, 2020). Strikingly, the EPC1-PHF1 fraction contained subunits of both the TIP60 and PRC2.1 complexes.…”
Section: Resultsmentioning
confidence: 88%
“…To date, pathways known to be associated with this gene include chromatin-modifying enzymes, chromatin organization, and histone acetyl transferases (HATs) [11]. Sophisticated studies have demonstrated that EPC1 is involved in constituting the NuA4 HAT complex, and the crystal structure and molecular basis for EPC1 bound to MBTD1 were determined [12]. Additionally, hsa_circ_0007919 knockdown can yield hsa-let-7a to downregulate EPC1 mRNA [13].…”
Section: Introductionmentioning
confidence: 99%